Studi Pengaruh Artificial Intelligence dan Teknologi Informasi Terhadap Minat Kerja Mahasiswa dengan Rekrutmen Digital Sebagai Mediator - Sahabuddin, Romansyah; Arif, Hery Maulana; Sari, Nabiilah Atiqah; Yuniarti, Iin; Syahrani, Aulia (Maksimal Jurnal : Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2024)
This research aims to find out how artificial intelligence and technology influence students' work interests by using intervening variables in the digital-based recruitment process. This research uses quantitative research with research data analysis which is multiple linear regression analysis with path analysis. With the aim of establishing whether a set of independent variables (exogenous) has a direct or indirect impact on the dependent variable, a path analysis model is used to evaluate the interaction pattern between variables (endogenous). The sampling method used in this research is non-probability sampling method with purposive sampling technique. Purposive sampling is a sample data collection technique that presents complete information data and uses certain considerations or criteria, namely 100 respondents. The results of this research prove that there is a positive direct influence between artificial intelligence and technology on students' work interest, as well as an indirect influence through digital-based recruitment process variables.